PENGARUH DOSIS PUPUK BIO ORGANIK CAIR TERHADAP PERTUMBUHAN SEMAI NYAWAI (Ficus variegata Blume) DI SHADE HOUSE - Muhammad Rizaldi Fajar; Dina Naemah; Mahrus Aryadi (Jurnal Sylva Scienteae, 2020)
The purpose of this study was to determine the effect of bio-organic fertilizer liquid on the growth of seedlings Nyawai (Ficus variegata Blume) in the case of high gain seedling, stem diameter and number of leaves. The expected benefits of this research is to be material information for those who want to develop Nyawai plant (Ficus variegata Blume) in the case of liquid organic bio fertilizers that provide the best growth. The method used is bio-organic fertilizer liquid fertilizer by providing an organic bio fertilizers are looking at a dose of 100, 150, and 200 m/1 liter of waterl.Nutrients contained therein are very subtle form of a solution that is easily absorbed by plants, such as leaves and stems. The results showed that the effect of liquid organic bio fertilizers have life percentage reaches 100%.The growth of stem height, stem diameter also increased and the number of leaves that are more and more, liquid organic bio fertilizers that provide the best growth of the seedlings nyawai is treated with a dose of 200 ml/1 liter of water.Keyword : Nyawai; Fertilizer; Bio Organic Liquid